Price Regulation in the Paper Industry - Guthrie, J. A. (Quarterly Journal of Economics, 1946)
The industry: definition, 194; characteristics, 195; structure, 196; economies of scale, 197. — Price regulation from World War I to the N.R.A.: newsprint, 198; book paper, 200; other branches, 201. — Price regulation during the N.R.A.: the newsprint code, 203; the general paper code, 204. — Price regulation after the N.R.A.: prewar developments, 206; war-time control, 210. — Summary, 211. — Some pertinent questions: restriction of price competition, 212; effects of price competition, 215; public policy, 216.